The potential achievement of weightlifting sport in Semarang through talent identification - Haryono, S.; Romadhoni, S.; Retno, E. S. (Advances in Social Science, Education and Humanities Research, 2019)
The purpose of this study is as an effort to improve sports performance by implementing and conducting a sports development program suited to the characteristics and potential of the region. So that efforts to identify superior sports are based on careful analysis of the potential, characteristics and conditions of the region towards improving sports performance. Sports coaching is inseparable from the existence of educational institutions which are expected to contribute and play a very significant role in achieving sports achievements. Based on the objectives, this approach was carried out to find out the talent of students in Semarang, especially in weightlifting Sports branch. The sample of the study was 199 students aged 10-12 years according to the criteria. This study used a quantitative approach with a percentage description method. Data collection technique was by measuring antropometrics tests, physiological tests and biomotor tests. The instruments used in this study were adjusted to the specific characteristics of weightlifting sports. The results of this study were from a sample of 199 students, 28 students (14.07%) had sports talent in Weightlifting sports. Conclusions from the results of this study indicate that there is a potential achievement of students who are talented in weightlifting sports in Semarang.